2003
DOI: 10.1096/fj.03-0317fje
|View full text |Cite
|
Sign up to set email alerts
|

Gene transcripts selectively down‐regulated in the shell of the nucleus accumbens long after heroin self‐administration are up‐regulated in the core independent of response contingency

Abstract: Long-term drug-induced alterations in neurotransmission within the nucleus accumbens (NAc) shell and core may underlie relapse to drug-seeking behavior and drug-taking upon re-exposure to drugs and drug-associated stimuli (cues) during abstinence. Using an open screening strategy, we recently identified 25 gene transcripts, encoding for proteins involved in neuronal functioning and structure that are down-regulated in rat NAc shell after contingent (active), but not after non-contingent (passive), heroin admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…These results are in line with previous studies demonstrating differential neuroadaptations in rats receiving heroin in a response-contingent vs -non-contingent manner (Kuntz et al, 2008;Jacobs et al, 2004;Jacobs et al, 2005), and these data may have particular importance for addiction and pain management fields, respectively. Interestingly, we also found that increases in NAc TacR1 mRNA following repeated (moderate dose) heroin was reduced following non-contingent, escalated-dose heroin exposure, possibly reflecting tolerance-associated changes in the NK1 receptor system.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with previous studies demonstrating differential neuroadaptations in rats receiving heroin in a response-contingent vs -non-contingent manner (Kuntz et al, 2008;Jacobs et al, 2004;Jacobs et al, 2005), and these data may have particular importance for addiction and pain management fields, respectively. Interestingly, we also found that increases in NAc TacR1 mRNA following repeated (moderate dose) heroin was reduced following non-contingent, escalated-dose heroin exposure, possibly reflecting tolerance-associated changes in the NK1 receptor system.…”
Section: Discussionsupporting
confidence: 91%
“…Inactivation of the NAc core, but not the shell, inhibits heroin self-administration (26) and heroin-induced reinstatement of drug-seeking behavior (K.M., unpublished data). Further, self-administration of heroin is associated with upregulation of gene transcripts involved in neuronal function within the NAc core but down-regulation of these same tran- scripts within the NAc shell (29). Notably, inactivation of the NAc core (but not shell) (19,30) or interference with prefrontal glutamatergic projections to the NAc core (20) also prevents cocaine-induced reinstatement of drug-seeking behavior (14).…”
Section: Discussionmentioning
confidence: 99%
“…Animals that self-administer vs receive opioids passively show differential electrophysiological activity of cells in the ventral tegmental area (Kiyatkin and Rebec, 2001) and prefrontal cortex (Lee et al, 1999), as well as differences in nucleus accumbens dopamine release (Hemby et al, 1995) and neurotransmitter turnover rates (Smith et al, 1980(Smith et al, , 1982(Smith et al, , 1984a. Chronic morphine SA relative to PA alters acetylcholine and benzodiazepine receptor density (Smith et al, 1984b), and the expression of various proteins (Self et al, 1995) and gene transcripts in the nucleus accumbens shell (Jacobs et al, 2002) but not nucleus accumbens core (Jacobs et al, 2004) relative to chronic PA.…”
Section: Introductionmentioning
confidence: 99%